Enhancing of cerebral Abeta clearance by modulation of ABC transporter expression: a review of experimental approaches - Loeffler, David A. (Frontiers in Aging Neuroscience, 2024)
Clearance of amyloid-beta (Ab) from the brain is impaired in both early-onset and late-onset Alzheimer's disease (AD). Mechanisms for clearing cerebral Ab include proteolytic degradation, antibody-mediated clearance, blood brain barrier and blood cerebrospinal fluid barrier efflux, glymphatic drainage, and perivascular drainage. ATP-binding cassette (ABC) transporters are membrane efflux pumps driven by ATP hydrolysis. Their functions include maintenance of brain homeostasis by removing toxic peptides and compounds, and transport of bioactive molecules including cholesterol. Some ABC transporters contribute to lowering of cerebral Ab. Mechanisms suggested for ABC transporter-mediated lowering of brain Ab, in addition to exporting of Ab across the blood brain and blood cerebrospinal fluid barriers, include apolipoprotein E lipidation, microglial activation, decreased amyloidogenic processing of amyloid precursor protein, and restricting the entrance of Ab into the brain. The ABC transporter superfamily in humans includes 49 proteins, eight of which have been suggested to reduce cerebral Ab levels. This review discusses experimental approaches for increasing the expression of these ABC transporters, clinical applications of these approaches, changes in the expression and/or activity of these transporters in AD and transgenic mouse models of AD, and findings in the few clinical trials which have examined the effects of these approaches in patients with AD or mild cognitive impairment. The possibility that therapeutic upregulation of ABC transporters which promote clearance of cerebral Ab may slow the clinical progression of AD merits further consideration.